Laser-Driven Structure-Based Accelerators - England, R. Joel; Filippetto, Daniele; Torrisi, Giuseppe; Bacci, Alberto; Della Valle, Giuseppe; Mascali, David; Mauro, Giorgio Sebastiano; Sorbello, G.; Musumeci, P.; Scheuer, Jakob; Cowan, B.; Schachter, L.; et al. (arXiv, 2022)
Particle acceleration in microstructures driven by ultrafast solid state lasers is a rapidly evolving area of advanced accelerator research, leading to a variety of concepts based on planar-symmetric dielectric gratings, hollow core fibers, photonic crystals, and plasmonic meta-surfaces. This approach leverages well-established industrial fabrication capabilities and the commercial availability of tabletop lasers to reduce cost, with demonstrated axial accelerating fields in the GV/m range. Wide-ranging international efforts have significantly improved understanding of gradient limits, structure design, particle focusing and transport, staging, and development of compatible low-emittance electron sources. With a near-term focus on low-current MeV-scale applications for compact scientific and medical instruments, as well as novel diagnostics capabilities, structure-based laser-driven accelerators have several key benefits that warrant consideration for future high-energy physics machines, including low beamstrahlung energy loss, modest power requirements, stability, and readiness of supporting technologies.